More than doubling the clinical benefit of each hour of therapist time: a randomised controlled trial of internet cognitive therapy for social anxiety disorder - Clark, DM; Wild, J; Warnock-Parkes, E; Stott, R; Grey, N; Thew, G; Ehlers, A (Cambridge University Press, 2022)
Background: Cognitive therapy for social anxiety disorder (CT-SAD) is recommended by NICE (2013) as a first line intervention. Take up in routine services is limited by the need for up to 14 ninety-minute face-to-face sessions , some of which are out of the office. An internet-based version of the treatment (iCTSAD) with remote therapist support may achieve similar outcomes with less therapist time.